Resource mobilization for Gender-Responsive Breeding - CGIAR Research Program on Roots, Tubers and Bananas (CGIAR System Organization, 2018)
This brief describes a strategy and work packages for the CGIAR Gender and Breeding Initiative (GBI) towards achieving the Initiative’s aim of enabling plant and animal breeding programs to be more gender-responsive.